Report on International Roundtable Meeting on Collection Security held at the British Library - Stephens, Andy; Shenton, Helen (LIBER Quarterly: The Journal of the Association of European Research Libraries, 2008)
Anonymised report on some of the issues raised at an international roundtable on collection security of thirteen major research libraries and national libraries from Europe and North America. Recurring themes of case studies included: 1) perpetrator profiling; 2) relations with the criminal justice system; 3) systems; 4) looking out; 5) aftermath.